Politics and Theology in the Homeric Hymn to Hermes - Vachninas, Benediktas (Literatūra, 2022)
The Homeric Hymn to Hermes depicts integration of newborn Hermes to Olympus and is devoted to his worship. However the glorifying character of the hymn conflicts with shameful acts of Hermes – the theft of Apollo’s cattles and the deception of Apollo and Zeus. That implies complexity of hymn’s glorified object. The article suggests to analyse the figure of Hermes in Hymn to Hermes by asking how it unrolls and what relation establishes with Apollo. This angle will not only locate connection between Hymn to Hermes and Hesiod’s Theogony, but also it will let unfold interaction amid Apollo and Hermes as relation of politics and theology in the order of Zeus.